The Application of Callista Roy Adaptation Model in the Care of Patients with Multiple Sclerosis – Case Report - Joanna Rosińczuk; Aleksandra Kołtuniuk; Magdalena Górska; Izabella Uchmanowicz (Pielęgniarstwo Neurologiczne i Neurochirurgiczne, 2015)
Introduction. Multiple sclerosis (Sclerosis Multiplex — MS) is a chronic disease of the central nervous system characterized by inflammation and the loss of myelin sheath surrounding the axon. A result of disseminated demyelination process in patients suffering from MS, is a wide variety of symptoms that lead to changes in terms of functioning both in biological and psychosocial aspects. The skilful preparation of a patient to find the optimal way of dealing with the disease, as well as maintaining independence and joy of life is an essential part of the therapeutic process in patients with MS. Aim. The aim of this study was to use the Callista Roy adaptation model in the care of a patient suffering from multiple sclerosis, namely: — demonstrate the usefulness of the holistic Callista Roy adaptation model in the care of chronically ill patients, — prepare a patient to cope with the problems induced by the disease, based on the nursing process developed in line ith the guidlines of C. Roy model. Case Report. A case study of a 69 year old patient with multiple sclerosis (SM) was prepared on the basis of medical documentation (personal information forms from hospitals), an interview with the patient and direct observations. Discussion. The nursing care model based on the theory by Callista Roy proved to be very useful in the process of taking care of a patient chronically ill with SM, as it guaranteed satisfying the needs of a patient in terms of bio-psychosocial aspect, but it also gave the opportunity to acquire skills to cope with problems resulting from the disease. Conclusions. The nursing process based on the theory by Callista Roy requires from a nurse an individual and holistic approach to a patient and patient’s problems. The model structure provides a comprehensive delivery of nursing care and ensures continuous contact with a patient. This is particularly important in the era of technology development in modern medicine. (JNNN 2015;4(3):121–129)